2015
DOI: 10.1055/s-0034-1396309
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Croton zehntneri and Its Main Constituent Anethole Block Excitability of Rat Peripheral Nerve

Abstract: Croton zehntneri is an aromatic plant native to Northeast Brazil and employed by local people to treat various diseases. The leaves of this plant have a rich content of essential oil. The essential oil of C. zehntneri samples, with anethole as the major constituent and anethole itself, have been reported to have several pharmacological activities such as antispasmodic, cardiovascular, and gastroprotective effects and inducing the blockade of neuromuscular transmission and antinociception. Since several works h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
(65 reference statements)
1
16
0
2
Order By: Relevance
“…277477) was deposited at the herbarium Prisco Viana of the Federal University of Cear a. The EOCz was extracted and isolated by steam distillation from leaves cut into small pieces and analyzed chemically as previously described [17,23].…”
Section: Plant Material Extraction and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…277477) was deposited at the herbarium Prisco Viana of the Federal University of Cear a. The EOCz was extracted and isolated by steam distillation from leaves cut into small pieces and analyzed chemically as previously described [17,23].…”
Section: Plant Material Extraction and Chemical Analysismentioning
confidence: 99%
“…It has recently been reported that anethole and estragole promote relaxation of rat corpora cavernosa with mechanism predominantly dependent on release of autacoids (NO and prostanoids) [22]. Also in rats, EOCz and anethole were able to block sciatic nerve compound action potentials with similar pharmacological potency [23].…”
Section: Introductionmentioning
confidence: 96%
“…For Croton zehntneri Pax et Hoffm. essential oil, the reduction was seen at a dose of 100 μ g/mL and IC 50 of 320 μ g/mL [ 25 ]. The Alpinia zerumbet (Pers.)…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, estudos de Croton mostraram que esses apresentam uma ampla gama de metabólitos secundários, como alcalóides (SUÁREZ et al, 2004), fenólicos (TALA, et al, 2013), terpenóides (AGUILAR-GUADARRAMA; RIOS, 2004;KUO et al, 2013 ) e óleos voláteis. (CAVALCANTI et al, 2012;SILVA-ALVES et al, 2015) Segundo estudos, 80% da população mundial pertencentes a países em desenvolvimento utilizam de medicina tradicional para o tratamento de diferentes tipos de doenças (NAGARAJAN, 1982).…”
Section: Referencial Teóricounclassified